Accuracy Analysis of GNSS Permanent Station Coordinates Using the Least Square Method by Processing Broadcast and Precise Ephemerides - Tanja Đukanović; Sanja Tucikešić; Biljana Antunović (AGG+, 2021)
This paper analyses how broadcast and precise ephemerides in alignment, using the least-squares method, affect the accuracy of coordinates of the newly included permanent stations. It has been shown that in practice, when аdjusting networks whose span between points exceeds 50 km, the adjustment procedure should be carried out using the adopted precise ephemerides for a specific observation period. Precise ephemerides are recommended for 30 to 50 km baseline lengths, while adjustments with broadcast ephemerides achieves satisfactory accuracy for shorter lengths. For baseline lengths of 30 to 50 km, the use of precise ephemerides is recommended, and for shorter lengths, adjustment with broadcast ephemerides achieves satisfactory accuracy. This paper analyses statistics and presents standard deviations of horizontal and vertical positions, when broadcast and precise ephemerides are applied.